Aspectos da capacidade vetorial e perfil de suscetibilidade ao temephós de populações de Aedes aegypti (Diptera: Culicidae) de diferentes regiões do estado de Sergipe, Brasil - Marteis, Letícia Silva (2012)
Ecology studies of Aedes aegypti are crucial to understand the behavior and adaptations made by the species according to their environment and that became evident during the evolutionary process due to different selective pressures facing the species in their origin environment. Therefore this study aimed to evaluate aspects of vectorial capacity and resistance to organophosphate temephos for Ae. aegypti from different regions of Sergipe. In addition to the resistance ratio of the populations to larvicides, developmental parameters and reproductive outcomes were duration of theimmature, number of pupae formed and adults emerged, sex ratio, survival of adults in different feeding conditions, fecundity of females, fertility eggs under stress climate, amount of blood ingested, the size of specimens and the occurrence of asymmetric wing. All evaluated populations of Ae. aegypti were resistance to temephos . The population from Neopolis, a city with favorable climatic characteristics for the development of species, showed a smaller ratio of the larvicide resistênicia and performance of developmental and reproductive variables evaluated. The population from Pinhão, which comes from the semi-arid, and has the highest resistance ratio to temephos, including outlier compared to those presented by other people, which was also exhibited greater loss in the parameters of vectorial capacity, with the exception of variable viability of eggs in a condition of environmental stress, for which the best performance. Thus, changes were observed in parameters of vectorial capacity which now seemed to be related to the climatic conditions of the original environment of the populations, probably due to adaptations developed by individuals, sometimes were related to the differents status of resistance to temephos observed.